Hannah Arendt: sobre la revolución - Wellmer, Albrecht (1998)
In her book On Revolution Hannah Arendt has tried to settle accounts with the two dominant political traditions of the Iast 150 years: liberal democrats and Marxists. According to her basic thesis, both traditions have misunderstood the actually revolutionary element in moder o revolutions: their repeatedly failed attempt to establish a constitutiolibertatis, that is, a political space of public freedom in which people as equal and free citizens would take control of their common concems. This paper tries to show how Arendt's apparently naive idea of direct or "council" democracy maybe used productively by being integrated into - instead of being opposed to-- the liberal-democratic socialist legacy.